2009
DOI: 10.1007/s12103-009-9069-z
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Race on the Pretrial Decision

Abstract: This study examined the effect of race on the pretrial release decision for drug offenders. Although this decision point has not been examined as extensively as the final sentencing decision, it is a critical discretion point which impacts defendants' future sentencing outcomes. The results found that race had a significant impact on judges' decisions to release a defendant on recognizance, with black defendants less likely to receive this release status. Race was not significant, however, in the decision of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 30 publications
(33 reference statements)
0
20
0
Order By: Relevance
“…Likewise, study findings on the effects of extralegal factors on pretrial custody decisions are also mixed. The effect of offenders' race on pretrial custody decisions has been the focus of growing empirical inquiry (see, e.g., Albonetti et al ; Ayres and Waldfogel ; Freiburger et al ), but the results are varied . In one study, Free (: 206–10) concluded that racial disparities in bond decisions are significant and have been stable over time, especially with respect to bond amounts.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Likewise, study findings on the effects of extralegal factors on pretrial custody decisions are also mixed. The effect of offenders' race on pretrial custody decisions has been the focus of growing empirical inquiry (see, e.g., Albonetti et al ; Ayres and Waldfogel ; Freiburger et al ), but the results are varied . In one study, Free (: 206–10) concluded that racial disparities in bond decisions are significant and have been stable over time, especially with respect to bond amounts.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Racial stereotypes linking race and ethnicity to criminality find that minority defendants are perceived as more dangerous, threatening and culpable than white defendants (Albonetti 1991(Albonetti , 1997Bridges and Crutchfield 1988;Bridges and Steen 1998;Farrell and Swigert 1978;Freiburger et al 2010;Kramer and Steffensmeier 1993;Miethe and Moore 1986;Steffensmeier and Demuth 2000;Steffensmeier et al 1998;Zatz 1984Zatz , 1985. Similarly, those individuals evaluated as committing the most serious crimes are more likely to be non-white Spohn, Gruhl and Welch 1981-82).…”
mentioning
confidence: 99%
“…Many pretrial detention studies focus on disparities across demographic factors (e.g., race, gender, and employment status) between those defendants who await adjudication behind bars and those that are out on bond during the pretrial period (Demuth, 2003;Frieburger, Marcum & Pierce, 2009;Holmes et al, 1987;McIntyre & Baradaran, 2013;Schlesinger, 2005).Focusing exclusively on drug offenders, Freiburger et al (2009) found that black defendants were more likely to be detained pretrial and females, though not found to be released more often than males, received lower bail amounts and those who were employed were more likely to be released.…”
Section: Background Literaturementioning
confidence: 99%